PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA PELECEHAN SEKSUAL (Studi di Polres Ngawi) - HUSNA, UMMUL (Dinamika Hukum, 2018)
The Cases of child sexual abuses are continues to increase over time. Children are the nation’s future generation who need special legal protection which is different from adults, because of their immaturity physical and mental reasons. The legal protection of children is defined as the legal protection to the children’s freedom and rights which is related to the welfare. The purpose of this research is to determine how the legal protection and the obstacle factors related to the crime of child sexual abuse victims in Ngawi. The method used in this research is empirical juridical approach with descriptive study. The data sources consists primary data and secondary data. The Data collected from literature study and interviews. Data were analyzed using qualitative approach, that is primary data obtained directly from the field analyzed according to the legislations which is related to the child protection. The results of the research are: (1) Implementation of legal protection against victims of sexual harassment in Ngawi Police Territory The implementation of legal protection against children as victims of sexual harassment has been in accordance with Presidential Decree No. 36/1990 on the Convention on the Rights of the Child. Research on the protection of child victims of sexual violence in polres ngawi year 2013-2015 above can be seen that the protection given to victims is to receive reports of victims of sexual violence against children under age so that it is in accordance with the law on child protection number 23 of 2002 as amended in law number 35 of 2014 (2) obstacles when conducting an investigation The barriers when conducting an investigation occur because first in terms of collecting evidence for sexual harassment cases there is no witness other than the victim himself who experienced it, the two victim's statements are not frankly due to fear, shame, trauma and the threat of the perpetrator. Keywords: law protection, victim of child sexual abuse